Strategi Perencanaan Pendidikan Islam - Sri Aisyah Amini; Jamilus Jamilus (Jurnal Dirosah Islamiyah, 2023)
Planning is a series of activities carried out in preparation for decision making about what should happen and what will be done. The importance of proper planning in the field of Islamic education, because Muslims consider Islamic education as the best way of life for a person. Ideally, Islamic education must have a good and systematic planning strategy so that Islamic education truly succeeds for all Muslims in the world and the hereafter. . If there is a planning strategy, it can lead the institution to the right and appropriate goals. The method used in this study is the type or approach of literature (Library Research). The data collection technique used in this study is the document technique, which seeks information about the topics discussed in the form of notes, books, publications or articles, magazines, and others. Keywords: Planning Strategy, Islamic Education